Environment-friendly black ink and preparation process thereof
By modifying the combination of water-based polyurethane and block copolymer dispersant, the problem of carbon black agglomeration in water-based inks is solved, and the ink is achieved with high gloss, excellent appearance quality and good durability.
Patent Information
- Application Number
- CN202510000355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The aqueous bonding material of carbon black in water-based ink is difficult to fully disperse, resulting in agglomeration of carbon black and affecting the layer flatness, durability and gloss of the ink.
Modified aqueous polyurethane as the linking material, and the capped PET oligomer was prepared by transesterification reaction, and 2-hydroxyethyl disulfide and PET oligomer were added to optimize light transmittance and water resistance, while acrylic stencils were used. The segment copolymer is used as a dispersant to improve the dispersion efficiency of carbon black.
It significantly reduces the agglomeration phenomenon of carbon black, improves the gloss, adhesion strength and wear resistance of the ink, and ensures that the ink still has high transparency and excellent appearance quality under low carbon black usage.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of inks, and in particular to an environmentally friendly black ink and a preparation process thereof. Background Art
[0002] Ink is an indispensable material in the printing industry, used to transfer information such as patterns and texts to substrates through printing or inkjet printing. The composition of ink mainly includes pigments, binders, fillers and additives, which are evenly mixed and repeatedly rolled to form a viscous colloidal fluid. The performance and quality of ink directly affect the appearance, durability and environmental protection of printed products. At present, the common types of ink mainly include solvent-based inks, water-based inks, UV inks and solid inks.
[0003] Among them, water-based ink is a kind of ink made of water-based resin as a binder. It contains almost no volatile organic compounds, has low harm to the environment and human health, has certain environmental protection significance, and is also suitable for a variety of printing methods. Therefore, water-based ink is an environmentally friendly, safe and efficient printing ink with a wide range of applications and superior performance. It is an important driving force for the printing industry's transformation to green manufacturing.
[0004] Currently, the most commonly used colorant is carbon black, which has good durability, abrasion resistance, environmental protection and hiding power, and is relatively cheap. A small amount can achieve the ideal coloring effect. However, when carbon black is combined with water-based ink, people have discovered a new problem. The water-based binder in the water-based ink is difficult to fully disperse the carbon black, and the carbon black will agglomerate to varying degrees in the system. In order to avoid the reduction of the flatness of the ink layer and the damage to durability (reduced friction resistance and adhesion) caused by agglomeration, the only way is to reduce the amount of carbon black, but this will seriously affect the gloss of the water-based ink, greatly reducing its appearance quality. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an environmentally friendly black ink and a preparation process thereof.
[0006] In the first aspect, the present application provides an environmentally friendly black ink, wherein the raw materials used include the following components in weight proportion: a binder 50-55wt%; a dispersant 1.5-2wt%; a colorant 10-15wt%; a filler 3-5wt%; a solvent 20-25wt%; and the balance is other additives; the dispersant is M w=11500-12600 block copolymer, the linker is modified waterborne polyurethane, and is prepared by the following method: I. PET material is subjected to ester exchange under the condition of adding a catalyst to form a blocked PET oligomer; II. 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide propylene oxide copolymer and isophorone diisocyanate are mixed in a weight ratio of (1.5-3): (0.6-2.5): 20: 11, a catalyst is added, and the reaction is performed to obtain a linker.
[0007] By adopting the above technical scheme, the present application firstly causes waste PET materials to undergo an ester exchange reaction under the condition of a catalyst to obtain PET oligomers terminated with neopentyl glycol (NPG) and dipropylene glycol (DPG), and then uses ethylene oxide propylene oxide copolymer and isophorone diisocyanate to prepare waterborne polyurethane, and then adds 2-hydroxyethyl disulfide and PET oligomers to optimize the light transmittance of the waterborne polyurethane. In addition, the present application strictly controls the addition amount of 2-hydroxyethyl disulfide and PET oligomer. If the addition amount of 2-hydroxyethyl disulfide and / or PET oligomer is too large, the light transmittance will decrease instead of increase, and if the addition amount is too small, the effect of effectively improving the light transmittance and water resistance cannot be achieved. The light transmittance of the finally obtained linking material in the wavelength range of 400-800nm is not less than 95.2%, and has a high light transmittance.
[0008] On this basis, the present application further reduces the amount of colorant (carbon black) added, thereby reducing the degree of agglomeration of carbon black in the system, and also adds an acrylic block copolymer as a dispersant, which can have an affinity anchoring effect with carbon black and use its own hydrophilic chain segment to fully improve the dispersion efficiency of carbon black in the system, further reducing the possibility of carbon black agglomeration in the system, thereby significantly improving the internal uniformity of the ink system, and then improving the gloss, adhesion strength and wear resistance of the ink layer formed after printing. Furthermore, the present application controls the average molecular weight M of the acrylic block copolymer. w , making its dispersion effect better. If the average molecular weight is too large, the dispersant itself will produce entanglement and folding, affecting its dispersion effect in the system, and the hydrophilic chain segment will also have excessive association effect with water, thereby weakening its auxiliary dispersion effect for carbon black; if the average molecular weight is too small, the anchoring efficiency between the dispersant and carbon black is insufficient, and it also cannot achieve a good dispersion effect.
[0009] In general, the present application has fully improved the agglomeration phenomenon of carbon black from two aspects of reducing the amount of carbon black used and improving the dispersion effect of carbon black. In addition, the high-transparency binder of the present application can ensure that the ink still has a high gloss and excellent appearance quality when the amount of carbon black used is reduced. The final environmentally friendly black ink is environmentally friendly, durable and has high gloss. Experimental data show that the adhesion rating of the environmentally friendly black ink of the present application can reach level II or above, the gloss can reach more than 82.6%, and the maximum number of frictions under a load of 200g can reach 138 times or more.
[0010] Preferably, in step II, the weight ratio of 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide / propylene oxide copolymer and isophorone diisocyanate is 2.31:1.24:20:11.
[0011] By adopting the above technical scheme, the present application further controls the weight ratio of 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide propylene oxide copolymer and isophorone diisocyanate, thereby further improving the transmittance and water resistance of the binder. Experimental data show that when the weight ratio is 2.31:1.24:20:11, the transmittance of the binder in the wavelength range of 400-800nm can reach more than 96.1%, and the water resistance of the final ink can reach Class I.
[0012] Preferably, the dispersant is prepared by the following method: methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether are mixed in a molar ratio of (1-2):1:(1-2), reacted under the protection of an inert gas and with the addition of a catalyst, cooled to room temperature, adjusted the pH to neutral, and distilled to obtain M w =11500-12600 dispersant.
[0013] By adopting the above technical scheme, the present application uses methacrylic acid, dimethylaminoethyl methacrylate, and allyl polyoxyethylene ether to form a block copolymer under certain conditions. The block copolymer has both hydrophilic segments and hydrophobic segments. While improving the dispersibility of carbon black, it can also make the system have a certain hydrophobicity. The final ink can have good internal uniformity and water resistance after spraying and curing.
[0014] Preferably, the allyl polyoxyethylene ether is APEG-500.
[0015] By adopting the above-mentioned technical scheme, the present application utilizes APEG-500 as the hydrophilic monomer in the dispersant among allyl polyoxyethylene ethers with different polymerization degrees. Experiments have proved that, under the average molecular weight and material molar ratio controlled by the present application, APEG-500 has a more suitable polymerization degree than allyl polyoxyethylene ethers with other polymerization degrees, and also has a more suitable hydrophilic chain segment length, which can further balance the effect of the dispersant in anchoring carbon black and its own dispersion effect, so that the ink has better wear resistance after spraying and curing.
[0016] Preferably, the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether is 1.5:1:1.5.
[0017] By adopting the above technical scheme, the present application further controls the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether to 1.5:1:1.5 on the basis of using APEG-500 as allyl polyoxyethylene ether, thereby optimizing the internal uniformity of the ink and the balance of water resistance. By strictly controlling the amount of methacrylic acid and allyl polyoxyethylene ether, the ratio of the hydrophilic segment to the hydrophobic segment of the dispersant is controlled. The appropriate hydrophilic segment can effectively improve the dispersion effect of carbon black and minimize its own aggregation in the aqueous system. The appropriate hydrophobic segment can improve the water resistance of the ink and avoid its own competitive association in the aqueous system as much as possible, thereby maintaining the water-oil balance of the ink. After testing, the water resistance level of the ink of the present application can reach Class I standard.
[0018] Preferably, the M of the dispersant w =12200.
[0019] By adopting the above technical scheme, the present application continuously monitors the molecular weight of the product of the dispersant during the reaction, and controls the average molecular weight of the dispersant finally obtained by quenching the reaction, thereby balancing the degree of dispersant's auxiliary effect on carbon black and its own dispersion degree. Experimental data show that when the present application controls the average molecular weight at 12200, the dispersant can achieve the best level of dispersion effect for itself and carbon black, and the adhesion fastness, wear resistance and glossiness are improved.
[0020] Preferably, the raw materials used include the following components in weight proportions: 54wt% of a binder; 1.75wt% of a dispersant; 12wt% of a colorant; 4wt% of a filler; 24wt% of a solvent; and the remainder is other additives.
[0021] In the second aspect, the present application provides a preparation process of an environmentally friendly black ink, comprising the following steps: premixing the dispersant, colorant, filler, solvent and half of the additives, adding the binder, grinding, and then adding the remaining half of the additives and mixing evenly to finally obtain the environmentally friendly black ink.
[0022] In summary, this application has the following beneficial technical effects: 1. The present application has fully improved the agglomeration of carbon black from two aspects: reducing the amount of carbon black used and improving the dispersion effect of carbon black. The high-transparency binder of the present application can ensure that the ink still has a high gloss and excellent appearance quality when the amount of carbon black used is reduced. The environmentally friendly black ink finally obtained has environmental protection, durability and high gloss. The experimental data show that the adhesion rating of the environmentally friendly black ink of the present application can reach level II or above, and the gloss can reach more than 82.6%; 2. This application strictly controls the ratio of hydrophilic segments to hydrophobic segments in the dispersant, the average molecular weight of the dispersant, and the degree of polymerization of allyl polyoxyethylene ether, so that the final ink can have good internal uniformity and water resistance after spray curing; 3. This application strictly controls the amount of 2-hydroxyethyl disulfide and PET oligomer added during the preparation of the binder, and simultaneously improves the light transmittance and water resistance of the binder, so that the final ink also has good water resistance and high gloss. DETAILED DESCRIPTION
[0023] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Butyl titanate was purchased from Shandong Jibei New Materials Co., Ltd.; 2-Hydroxyethyl disulfide Shandong Xiya Chemical; Ethylene oxide propylene oxide copolymer was purchased from Sigma-Aldrich, CAS No. 9003-11-6, average molecular weight 5800, and placed in a vacuum drying oven at 0.8 MPa and 110 °C for 2 h before use to complete preliminary drying and set aside; Polytetrahydrofuran was purchased from Hubei Shineng Chemical Technology Co., Ltd., model PTMEG-2000, and was placed in a vacuum drying oven at 0.8 MPa and 110 °C for 2 h before use to complete preliminary drying and set aside; Tetrahydrofuran ethylene oxide polymer was purchased from Kinbester Co., Ltd., CAS No. 27637-03-2. Before use, it was placed in a vacuum drying oven at 0.8 MPa and 110°C for 2 h to complete preliminary drying and set aside; Boron trifluoride etherate, propylene oxide, tetrahydrofuran, and 1,2-propylene glycol were purchased from Sinopharm Chemical Reagent Co., Ltd. of analytical grade; Isophorone diisocyanate was purchased from Anhui Jinyueguan New Material Technology Co., Ltd.; Dibutyltin dilaurate was purchased from Jinan Hongboli Chemical Co., Ltd.; Methacrylic acid was purchased from Sinopharm Group Co., Ltd.; Isopropanol was purchased from Shanghai Lingfeng Chemical Reagent Co., Ltd.; n -Dodecyl mercaptan was purchased from Chevron Phillips Chemical Co.; Azobisisobutyronitrile was purchased from Sinopharm Group Co., Ltd.; Dimethylaminoethyl methacrylate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., analytical grade; APEG-300, APEG-500, and APEG-700 were customized by Jiangsu Haian Petrochemical Plant, with an active ingredient content of 99wt%; Hydrophilic titanium dioxide was purchased from Jiangsu Hehai Nanotechnology Co., Ltd., model NY-010A; Carbon black was purchased from Tianjin Baochi Chemical Technology Co., Ltd., with a D50 of 8 um and a carbon content of ≥99.9 wt%; The wetting agent was purchased from Hangzhou Lin'an Digao Organic Chemical Co., Ltd., model TEGO-245; The leveling agent was purchased from BYK Chemicals, model number BYK-306; The drying agent was purchased from Shanghai Tianyu Chemical Technology Co., Ltd., model A-16; The defoamer was purchased from Xipusen New Materials (Ningbo) Co., Ltd., model DF800; Waterborne polyurethane was purchased from Hefei Anke Fine Chemical Co., Ltd., model PU144.
[0024] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0025] Preparation Example 1.1 The method for preparing the linking material comprises the following steps: I. The waste PET material was washed and cut into 1 cm*1 cm fragments, and then washed alternately in 1 mol / L HCl solution and 5 mol / L NaOH solution for three times, and then washed in deionized water for three times, and vacuum dried to obtain PET fragments, and then the PET fragments were mixed with NPG and DPG in a molar ratio of 1:1.5:1.5, and preheated for 1 h at a temperature of 160°C and a stirring speed of 250 rpm, and then butyl titanate was added in an amount of 0.05 wt% of the total amount of the PET fragments, and stirring was continued for 3.5 h, and then the speed was adjusted to 500 rpm and kept warm for 30 min, and the stirring was turned off when the temperature of the reaction system dropped to room temperature, and the system was dried to a constant weight, and finally PET oligomers capped with NPG and DPG were obtained; II. Mix 200 g of the dried ethylene oxide propylene oxide copolymer and 111 g of isophorone diisocyanate, stir at 250 rpm for 1 h, then add 4 mg of dibutyltin dilaurate, react at 80 ° C for 2 h to obtain a prepolymer, reduce the temperature to 50 ° C, add 15 g of 2-hydroxyethyl disulfide and 25 g of the PET oligomer obtained in step I, continue stirring for 3 h to obtain a binder, and its transmittance in the wavelength range of 400-800 nm is tested to be 95.2-95.8%.
[0026] Preparation Example 1.2 The method for preparing the linking material comprises the following steps: I. The waste PET material was washed and cut into 1 cm*1 cm fragments, and then washed alternately in 1 mol / L HCl solution and 5 mol / L NaOH solution for three times, and then washed in deionized water for three times, and vacuum dried to obtain PET fragments, and then the PET fragments were mixed with NPG and DPG in a molar ratio of 1:1.5:1.5, and preheated for 1 h at a temperature of 160°C and a stirring speed of 250 rpm, and then butyl titanate was added in an amount of 0.05 wt% of the total amount of the PET fragments, and stirring was continued for 3.5 h, and then the speed was adjusted to 500 rpm and kept warm for 30 min, and the stirring was turned off when the temperature of the reaction system dropped to room temperature, and the system was dried to a constant weight, and finally PET oligomers capped with NPG and DPG were obtained; II. Mix 200 g of the dried ethylene oxide propylene oxide copolymer and 111 g of isophorone diisocyanate, stir at 250 rpm for 1 h, then add 4 mg of dibutyltin dilaurate, react at 80° C. for 2 h to obtain a prepolymer, lower the temperature to 50° C., add 30 g of 2-hydroxyethyl disulfide and 6 g of the PET oligomer obtained in step I, and continue stirring for 3 h to obtain a binder. The transmittance of the binder in the wavelength range of 400-800 nm is 95.5-95.9% after testing.
[0027] Preparation Example 1.3 The preparation method of the binder is different from that of Preparation Example 1.1 in that: in step II, the amount of 2-hydroxyethyl disulfide used is 23.1 g, the amount of PET oligomer obtained in step I is 12.4 g, and the rest is the same as in Preparation Example 1.1, to obtain a binder, and its transmittance in the wavelength range of 400-800nm is tested to be 96.1-97.0%.
[0028] Preparation Example 2.1 The preparation method of the dispersant comprises the following steps: First, methacrylic acid, dimethylaminoethyl methacrylate, APEG-300 and azobisisobutyronitrile are mixed in a molar ratio of 2:1:1:0.04, dispersed in an isopropanol solvent containing n-dodecyl mercaptan, wherein the content of n-dodecyl mercaptan is 1‰ of the total mass of methacrylic acid, dimethylaminoethyl methacrylate, APEG-300 and azobisisobutyronitrile, and the temperature is raised to reflux under nitrogen protection, and then the premixed solution is added dropwise, and the addition is completed within 180 minutes. After keeping the temperature at 65°C for 1 hour, azobisisobutyronitrile is added in an amount that is the same as the initial addition amount. After the addition is completed, the temperature is kept for reaction, and the molecular weight of the product is monitored at any time during the reaction. When M w =11500, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0029] Preparation Example 2.2 The preparation method of the dispersant comprises the following steps: First, methacrylic acid, dimethylaminoethyl methacrylate, APEG-300 and azobisisobutyronitrile are mixed in a molar ratio of 1:1:2:0.04, dispersed in an isopropanol solvent containing n-dodecyl mercaptan, wherein the content of n-dodecyl mercaptan is 1‰ of the total mass of methacrylic acid, dimethylaminoethyl methacrylate, APEG-300 and azobisisobutyronitrile, and the temperature is raised to reflux under nitrogen protection, and then the premixed solution is added dropwise, and the addition is completed within 180 minutes. After keeping the temperature at 65°C for 1 hour, azobisisobutyronitrile is added in an amount that is the same as the initial addition amount. After the addition is completed, the temperature is kept for reaction, and the molecular weight of the product is monitored at any time during the reaction. When M w =12600, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0030] Preparation Example 3.1 The preparation method of the dispersant is different from that of Preparation Example 2.1 in that APEG-300 is replaced by APEG-500, and the rest is the same as Preparation Example 2.1.
[0031] Preparation Example 3.2 The preparation method of the dispersant is different from that of Preparation Example 2.1 in that APEG-300 is replaced by APEG-700, and the rest is the same as Preparation Example 2.1.
[0032] Preparation Example 4.1 The preparation method of the dispersant is different from that of Preparation Example 3.1 in that the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate, APEG-500 and azobisisobutyronitrile is 1:1:1:0.03, and the rest is the same as Preparation Example 3.1.
[0033] Preparation Example 4.2 The preparation method of the dispersant is different from that of Preparation Example 3.1 in that the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate, APEG-500 and azobisisobutyronitrile is 2:1:2:0.05, and the rest is the same as Preparation Example 3.1.
[0034] Preparation Example 4.3 The preparation method of the dispersant is different from that of Preparation Example 3.1 in that the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate, APEG-500 and azobisisobutyronitrile is 1.5:1:1.5:0.04, and the rest is the same as Preparation Example 3.1.
[0035] Preparation Example 5.1 The preparation method of the dispersant is different from that of Preparation Example 4.3 in that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =11800, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0036] Preparation Example 5.2 The preparation method of the dispersant is different from that of Preparation Example 4.3 in that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =12000, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and after diluting with water, it was distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0037] Preparation Example 5.3 The preparation method of the dispersant is different from that of Preparation Example 4.3 in that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =12200, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0038] Preparation Example 5.4 The preparation method of the dispersant is different from that of Preparation Example 4.3 in that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =12400, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0039] Comparative Preparation Example 1.1 The difference from Preparation Example 1.2 is that in step II, the amount of 2-hydroxyethyl disulfide used is 35 g, the amount of PET oligomer obtained in step I used is 30 g, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800 nm is 83.0-83.6%.
[0040] Comparative Preparation Example 1.2 The difference from Preparation Example 1.2 is that in step II, the amount of 2-hydroxyethyl disulfide used is 10 g, the amount of PET oligomer obtained in step I used is 5 g, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800 nm is 80.2-80.5%.
[0041] Comparative Preparation Example 2.1 The difference from Preparation Example 1.2 is that in step II, 2-hydroxyethyl disulfide is removed, the amount of PET oligomer obtained in step I is 36 g, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800nm is 81.9-82.4%.
[0042] Comparative Preparation Example 2.2 The difference from Preparation Example 1.2 is that in step II, the PET oligomer obtained in step I is removed, the amount of 2-hydroxyethyl disulfide is 36 g, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800nm is 83.5-84.1%.
[0043] Comparative Preparation Example 3.1 The difference from Preparation Example 2.1 is that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =10500, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0044] Comparative Preparation Example 3.2 The difference from Preparation Example 2.1 is that: after adding azobisisobutyronitrile, the reaction is continued, and the molecular weight of the product is monitored at any time during the reaction. w =13200, the system was cooled to room temperature and ammonia water was added to neutralize the system until it was neutral to quench the reaction, and then diluted with water and distilled under reduced pressure until the system had a constant weight to obtain a dispersant.
[0045] Comparative Preparation Example 4.1 The difference from Preparation Example 1.2 is that the ethylene oxide propylene oxide copolymer in step II is replaced by polytetrahydrofuran, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800nm is 89.7-90.3%.
[0046] Comparative Preparation Example 4.2 The difference from Preparation Example 1.2 is that the ethylene oxide propylene oxide copolymer in step II is replaced by a tetrahydrofuran ethylene oxide polymer, and the rest is the same as Preparation Example 1.2. The transmittance of the obtained binder in the wavelength range of 400-800nm is 87.9-88.5%.
[0047] Comparative Preparation Example 4.3 The difference from Preparation Example 1.2 is that the ethylene oxide propylene oxide copolymer in step II is replaced by a tetrahydrofuran propylene oxide polymer, and the rest is the same as Preparation Example 1.2. The light transmittance of the obtained binder in the wavelength range of 400-800nm is 92.0-92.4%; The tetrahydrofuran propylene oxide polymer is prepared according to the description in the article "Synthesis Research of Tetrahydrofuran-Propylene Oxide Copolyether" by He Zhiqiang [D]. Jiangnan University, 2009. Specifically, tetrahydrofuran, 1,2-propylene glycol and boron trifluoride ether are mixed, stirred, cooled to -5°C in an ice-salt bath, and propylene oxide is added dropwise at a dropping rate of 0.21g / min. After the addition is completed, the reaction is continued at a temperature of -5°C for 3h to obtain a tetrahydrofuran propylene oxide polymer with an average molecular weight of 2990, wherein the amount of boron trifluoride ether is 2.5wt% of the total amount of tetrahydrofuran and propylene oxide, and the molar ratio of 1,2-propylene glycol, tetrahydrofuran and propylene oxide is 0.057:2:1.
[0048] Example 1.1 A process for preparing an environmentally friendly black ink comprises the following steps: The dispersant, carbon black, hydrophilic titanium dioxide, distilled water and half of the additives prepared in Preparation Example 2.1 were mixed, premixed at a speed of 360 rpm for 10 minutes, and after premixing evenly, the binder prepared in Preparation Example 1.2 was added, ball milled for 2 hours, and after filtering out the grinding balls, the remaining half of the additives were added and mixed evenly to finally obtain an environmentally friendly black ink. The amount of each component is shown in Table 1.
[0049] Example 1.2 A process for preparing an environmentally friendly black ink comprises the following steps: The dispersant, carbon black, hydrophilic titanium dioxide, distilled water and half of the additives prepared in Preparation Example 2.2 were mixed, premixed at a speed of 360 rpm for 10 minutes, and after premixing evenly, the binder prepared in Preparation Example 1.1 was added, ball milled for 2 hours, and after filtering out the grinding balls, the remaining half of the additives were added and mixed evenly to finally obtain an environmentally friendly black ink. The amount of each component is shown in Table 1.
[0050] Example 1.3 A process for preparing an environmentally friendly black ink comprises the following steps: The dispersant, carbon black, hydrophilic titanium dioxide, distilled water and half of the additives prepared in Preparation Example 2.1 were mixed, premixed at a speed of 360 rpm for 10 minutes, and after premixing evenly, the binder prepared in Preparation Example 1.2 was added, ball milled for 2 hours, and after filtering out the grinding balls, the remaining half of the additives were added and mixed evenly to finally obtain an environmentally friendly black ink. The amount of each component is shown in Table 1.
[0051] Table 1 Amount of each component used in Examples 1.1-1.3 / kg
[0052] Example 2 A preparation process of an environmentally friendly black ink, which is different from Example 1.1 in that the binder prepared in Preparation Example 1.2 is replaced by the binder prepared in Preparation Example 1.3, and the rest is the same as Example 1.1.
[0053] Examples 3.1-3.2 A preparation process of an environmentally friendly black ink, which is different from Example 1.1 in that the dispersants prepared in Preparation Example 2.1 are replaced by the dispersants prepared in Preparation Examples 3.1-3.2 respectively, and the rest is the same as Example 1.1.
[0054] Examples 4.1-4.3 A preparation process of an environmentally friendly black ink, which is different from Example 3.1 in that the dispersants prepared in Preparation Example 3.1 are replaced by the dispersants prepared in Preparation Examples 4.1-4.3 respectively, and the rest is the same as Example 3.1.
[0055] Examples 5.1-5.4 A preparation process of an environmentally friendly black ink, which is different from Example 4.3 in that the dispersants prepared in Preparation Example 4.3 are replaced by the dispersants prepared in Preparation Examples 5.1-5.4 respectively, and the rest is the same as Example 4.3.
[0056] Comparative Example 1.1 The difference from Example 1.1 is that the binder prepared in Preparation Example 1.2 is replaced by water-based polyurethane, and the rest is the same as Example 1.1.
[0057] Comparative Example 1.2-1.5 The difference from Example 1.1 is that the binder prepared in Preparation Example 1.2 is replaced by the binder prepared in Comparative Preparation Examples 1.1-2.2 respectively, and the rest is the same as Example 1.1.
[0058] Comparative Example 2.1 The difference from Example 1.1 is that the dispersant prepared in Preparation Example 2.1 is removed, the amount of carbon black used is 7.5 kg, and the rest is the same as Example 1.1.
[0059] Comparative Examples 2.2-2.3 The difference from Example 1.1 is that the dispersants prepared in Preparation Example 2.1 are replaced by the dispersants prepared in Comparative Preparation Examples 3.1-3.2 respectively, and the rest is the same as Example 1.1.
[0060] Comparative Examples 3.1-3.3 The difference from Example 1.1 is that the binder prepared in Preparation Example 1.2 is replaced by the binder prepared in Comparative Preparation Examples 4.1-4.3 respectively, and the rest is the same as Example 1.1.
[0061] Performance Testing
[0062] The ink samples prepared in the examples and comparative examples were sprayed and cured on PET as a substrate, and dried for 24 hours to prepare printed samples with an ink layer printed on the surface, and the following tests were performed: 1. Detect the glossiness of the ink layer according to the record in standard GB / T 9754-2007, and record the results in Table 2; 2. Detect the adhesion fastness grade of the ink layer according to the record in standard GB / T 13217.7-2023 (Grade I is the best), and record the results in Table 2; 3. Use a friction fastness tester to rub the sample under a load of 200g, observe the shedding of the ink layer, and record the maximum number of frictions at which the ink layer does not fall off in Table 2; 4. Detect the water resistance level of the ink layer according to the record in standard GB / T 1733-1993 (level I is the best), and record the results in Table 2.
[0063] Table 2 Performance test results
[0064] Data Analysis: As can be seen from Table 2, the ink layer formed by the ink prepared in Examples 1.1-1.3 of the present application after spray curing has a gloss of 82.6-83.2%, a maximum friction number of 138-147 times under a load of 200g, an adhesion fastness of II, and a water resistance of II, which proves that the present application has fully improved the agglomeration of carbon black from the two aspects of reducing the amount of carbon black and improving the dispersion effect of carbon black, and the high-transparency binder of the present application can ensure that the ink still has a high gloss when the amount of carbon black is reduced, and has excellent appearance quality. The environmentally friendly black ink finally obtained has both environmental protection, durability and high gloss; The glossiness and water resistance of the ink layer formed by the ink prepared in Example 2 after spraying and curing are significantly better than those in Example 1.1, proving that the present application further improves the light transmittance and water resistance of the binder by strictly controlling the weight ratio of 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide propylene oxide copolymer and isophorone diisocyanate; The maximum friction times and adhesion strength of the ink layer formed by the ink prepared in Example 3.1 after spray curing are significantly better than those in Example 1.1 and Example 3.2, proving that the APEG-500 of the present application has a more suitable degree of polymerization than allyl polyoxyethylene ethers of other degrees of polymerization, and thus has a more suitable hydrophilic chain length, which can further balance the effect of the dispersant anchoring carbon black and its own dispersion effect, and can make the ink have better wear resistance after spray curing; The ink layer formed by the ink prepared in Example 4.3 after spray curing has excellent performance indicators, which proves that the present application controls the ratio of the hydrophilic segment to the hydrophobic segment of the dispersant by strictly controlling the molar ratio of methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether. The appropriate hydrophilic segment can effectively improve the dispersion effect of carbon black and minimize its own aggregation in the aqueous system, while the appropriate hydrophobic segment can improve the water resistance of the ink and avoid its own competitive association in the aqueous system as much as possible, thereby maintaining the water-oil balance of the ink and optimizing the internal uniformity of the ink and the balance of water resistance; The ink prepared in Example 5.3 has better performance indicators than those in Example 4.3, Example 5.1-5.2 and Example 5.4 after spray curing, which proves that the present application controls the average molecular weight of the dispersant finally obtained by monitoring the molecular weight and controlling the reaction time, thereby balancing the degree of dispersant's auxiliary effect on carbon black and its own dispersion, so that the dispersing effect of itself and carbon black reaches the best level, and the adhesion, abrasion resistance and glossiness are improved; The glossiness of the ink layer formed by the ink prepared in Comparative Example 1.1 after spray curing is only 70.8%, which is much lower than that of Example 1.1. This proves that the present application optimizes the light transmittance of the waterborne polyurethane by using 2-hydroxyethyl disulfide and PET oligomer, and can maintain the good glossiness of the ink layer under the premise of reducing the amount of carbon black to ensure the dispersion of carbon black, so that its appearance quality is guaranteed; The glossiness of the ink layers formed by the inks prepared in Comparative Examples 1.2-1.5 after spray curing is inferior to that of Example 1.1, which proves that the present application simultaneously uses 2-hydroxyethyl disulfide and PET oligomer to modify the waterborne polyurethane, which can effectively improve its light transmittance, and 2-hydroxyethyl disulfide and PET oligomer have a good synergistic effect, which can jointly improve the light transmittance and water resistance of the binder; The maximum friction number of the ink layer formed by the ink prepared in Comparative Example 2.1 after spray curing is only 95 times, and the adhesion strength is only IV level. The amount of carbon black in Comparative Example 2.1 has been reduced by 25wt% on the basis of Example 1.1, but the uniformity in the system is still low, which proves that the dispersant of the present application can indeed greatly improve the dispersibility of carbon black in the system, making the dispersion uniformity inside the ink higher; The maximum friction times and adhesion strength of the ink layer formed by the ink prepared in Comparative Examples 2.2-2.3 after spray curing are inferior to those in Example 1.1, which proves that the present application controls the average molecular weight of the dispersant finally obtained by monitoring the molecular weight and controlling the reaction time, thereby balancing the degree of dispersant's auxiliary dispersion of carbon black and its own dispersion degree, and improving the dispersion uniformity inside the ink; The glossiness of the ink layer formed by the ink prepared in Comparative Examples 3.1-3.3 after spray curing is significantly lower than that in Example 1.1, proving that the aqueous polyurethane prepared by using ethylene oxide propylene oxide copolymer and isophorone diisocyanate in the present application, after being combined with PET oligomer, has the highest light transmittance, which makes the glossiness of the final ink the best.
[0065] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An environmentally friendly black ink, characterized in that: The raw materials used include the following components in weight proportion: binder 50-55wt%; dispersant 1.5-2wt%; colorant 10-15wt%; filler 3-5wt%; solvent 20-25wt%; the balance is other additives; the dispersant is M w =11500-12600 block copolymer, the linking material is modified waterborne polyurethane, prepared by the following method:
1. Transesterifying the PET material under the condition of adding a catalyst to form a capped PET oligomer; II. Mix 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide propylene oxide copolymer and isophorone diisocyanate in a weight ratio of (1.5-3): (0.6-2.5): 20: 11, add a catalyst, and react to obtain a binder.
2. The environmentally friendly black ink according to claim 1, characterized in that: In the step II, the weight ratio of 2-hydroxyethyl disulfide, PET oligomer, ethylene oxide propylene oxide copolymer and isophorone diisocyanate is 2.31:1.24:20:
11.
3. The environmentally friendly black ink according to claim 1, characterized in that: The dispersant is prepared by the following method: Methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether were mixed in a molar ratio of (1-2):1:(1-2), reacted under the protection of inert gas and with the addition of a catalyst, cooled to room temperature, adjusted to a neutral pH, and distilled to obtain M w =11500-12600 dispersant.
4. The environmentally friendly black ink according to claim 3, characterized in that: The allyl polyoxyethylene ether is APEG-500.
5. The environmentally friendly black ink according to claim 4, characterized in that: The molar ratio of methacrylic acid, dimethylaminoethyl methacrylate and allyl polyoxyethylene ether is 1.5:1:1.
5.
6. The environmentally friendly black ink according to claim 5, characterized in that: The M of the dispersant w =12200.
7. The environmentally friendly black ink according to claim 1, characterized in that: The raw materials used include the following components in proportion by weight: 54wt% binder; 1.75wt% dispersant; 12wt% colorant; 4wt% filler; 24wt% solvent; and the balance is other additives.
8. A process for preparing the environmentally friendly black ink according to any one of claims 1 to 7, characterized in that: The following steps are involved: The dispersant, colorant, filler, solvent and half of the additives are premixed evenly, and then the binder is added and ground, and then the remaining half of the additives are added and mixed evenly to finally obtain an environmentally friendly black ink.
Citation Information
Patent Citations
Method for synthetizing aqueous polyurethane emulsion from package waste PET bottles
CN103865028A
Anti-dazzle polyurethane acrylate UV-curable resin composition of water-borne hyperbranched structure and preparation method thereof
CN108727557A
Preparation method of modified polyurethane emulsion for waterborne inks, modified polyurethane emulsion, waterborne ink and preparation method of waterborne ink
CN109824844A
Thermoplastic self-repairing polyurethane resin for 3D printing composite materials and preparation method thereof
CN110105532A
Block copolymerization self-repairing polyurethane anticorrosive coating as well as synthesis method and application thereof
CN111704854A
